The Effectiveness of Soft Liquor Product Placement as a Dark Marketing Strategy and Its Influence on Consumer Purchase Intention. - Md. Amran Hossain; Mendis Sanoj; Perera Nilantha (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2024)
Product placement is a promotional strategy which can be identified as a purposeful incorporation of product into an influential manner with a use of any other media. However, most of the countries have prohibited advertising soft liquor products via traditional media because of health issues caused by soft liquor products. Thus, the soft liquor manufacturers tended to invest in product placement. This paper reports the findings of how product placement influence on consumer purchases intention of soft liquor products. The study has focused on investigating the possible reasons for consumers to influence on product placement strategies and the product elements that they exposed to and used to, even in the presence of a wider range. Suggestions for further research are presented in the form of propositions.